Sweden : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sweden. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that Sweden's economy has performed well, but is sensitive to global demand. The activity is now moderating. Exports have benefited from sound competitiveness, but euro area and U.S. slowing is causing them to decelerate. Private consumption growth has been relatively smooth, as employment and wages have picked up, and disposable income further benefited from tax cuts. Employment growth reached 2 percent, and the unemployment rate declined from 8 percent in 2005 to 6 percent in early 2008.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet